CT and MR imaging of gastrointestinal stromal tumor of stomach: a pictorial review - Gong, Jingshan (AME Publishing Company, 2012)
This pictorial review illustrates CT and MR imaging appearance of gastrointestinal stromal tumor (GIST) of the stomach and other lesions with similar imaging appearance. GIST of the stomach appears as well-defined enhanced masses with characteristics of subeppthial neoplasms. Majority are exophytic growth, but can also be of intra-luminal growth. GIST can growth into a large mass without gastrointestinal tract obstruction. Necrosis is often seen in GIST and results in heterogeneous enhancement and communication with gastrointestinal tract. CT and MRI features of several other neoplasms mimicking GISTs in the stomach are also described in this review.